Effects of a community-based neonatal care package program. Issue 4 (19th March 2018) - Acharya, Yubraj
Abstract: This article evaluates a community-based effort aimed at reducing neonatal mortality. I use nationally representative data from Nepal, where 22 children per 1000 die within the first month of their birth, and evaluate the impact of Community-Based Neonatal Care Package. The identification is based on a before-and-after comparison of outcomes in program districts relative to those in non-program districts. I find that the program was successful in encouraging cleaner deliveries for births that took place at home and in increasing prenatal visits to the health center by pregnant women significantly. Despite these positive effects on intermediate outcomes, there is no evidence that the program reduced neonatal mortality. There is also no evidence that the program improved other intermediate outcomes, namely institutional or professional-attended deliveries. While the lack of an effect on a few of the outcomes may be mainly due to supply-side constraints, the findings also suggest the need for a broader examination of the role of the Female Community Health Volunteers.